Hematologies : the political life of blood in India - Copeman, Jacob; Banerjee, Dwaipayan, 1983- (Cornell University Press, 2019)
"Hematologies examines how the giving and receiving of blood has shaped social and political life in north India in the twentieth and twenty-first centuries"--